E-Learning-Based Islamic Education Learning (Innovation Study of MTsN 1 SAHAHLUNTO Educators in the Middle of the Covid-19 Outbreak) - firma Adinda; Fadriati Fadriati; Doni Warman (al-fikrah: Jurnal Manajemen Pendidikan, 2021)
This study aims to analyze: 1) policies related to distance learning during the Covid-19 emergency, 2) various learning innovations applied by PAI teachers, 3) obstacles faced by Islamic religious education teachers during distance learning. This research was conducted at MTsN 1 Sawahlunto. The research method used is a qualitative descriptive method, the primary data source of the research is the PAI subject teacher at MTsN 1 Sawahlunto with qualitative data collection techniques, using interview, observation and documentation techniques. The data analysis technique used is descriptive qualitative data analysis technique. The results showed that the policies implemented in MTs. Islamic Religious Education During the Covid-19 emergency period is to continue to carry out learning, but with a distance system based on an internet network. This policy is implemented in accordance with local government regulations. The various learning innovations applied are 1) Innovations in intracurricular activities, including the presentation of learning with multimedia, PAI learning that emphasizes the friendly motto, online-based discussions and assignments, application of project-based methods, activity-based learning evaluations. 2) Innovation in extracurricular activities, namely the routine of reading and memorizing the Qur'an. The obstacles faced were 1) mindset errors, 2) lack of competence, 3) unpreparedness of teachers and students in facing E-Learning learning